Diagnosis of mixed infection and a primary immunodeficiency disease using next-generation sequencing: a case report - Zhang, Xiaolei; Wang, Yixue; Pen, Daly; Liu, Jing; Zhou, Qinhua; Wang, Yao; Zhong, Huaqing; Liu, Tingyan; Chen, Weiming; Wu, Bingbing; Zhou, Yang; Wang, Chuanqing; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Major Histocompatibility Complex Class II (MHC II) deficiency is a rare primary immunodeficiency disorder (PID) with autosomal recessive inheritance pattern. The outcome is almost fatal owing to delayed diagnosis and lacking of effective therapy. Therefore, prompt diagnosis, timely and effective treatment are critical. Here, we report a 117-day-old boy with diarrhea, cough, cyanosis and tachypnea who was failed to be cured by empiric antimicrobial therapy initially and progressed to severe pneumonia and respiratory failure. The patient was admitted to the pediatric intensive care unit (PICU) immediately and underwent a series of tests. Blood examination revealed elevated levels of inflammatory markers and cytomegalovirus DNA. Imaging findings showed signs of severe infection of lungs. Finally, the diagnosis was obtained mainly through next-generation sequencing (NGS). We found out what pathogenic microorganism he was infected via repeated conventional detection methods and metagenomic next-generation sequencing (mNGS) of sputum and bronchoalveolar lavage fluid (BALF). And his whole exome sequencing (WES) examination suggested that CIITA gene was heterozygous mutation, a kind of MHC II deficiency diseases. After aggressive respiratory support and repeated adjustment of antimicrobial regimens, the patient was weaned from ventilator on the 56th day of admission and transferred to the immunology ward on the 60th day. The patient was successful discharged after hospitalizing for 91 days, taking antimicrobials orally to prevent infections post-discharge and waiting for stem cell transplantation. This case highlights the potential importance of NGS in providing better diagnostic testing for unexplained infection and illness. Furthermore, pathogens would be identified more accurately if conventional detection techniques were combined with mNGS.